Discursive strategies that foster an epistemic community for argument in a biology classroom. (April 2017) - Forman, Ellice Ann; Ramirez-DelToro, Virginia; Brown, Lisa; Passmore, Cynthia
Abstract: Although the study of classroom discourse has a long history, there has been a recent change in theoretical perspective towards viewing learning as becoming a member of a disciplinary community. In science classrooms, teachers are attempting to create epistemic communities that include some of the characteristics of scientific communities. Using this theoretical lens, we describe how an experienced classroom teacher used discursive moves to scaffold her students' appropriation of scientific argumentation over several weeks. As her prompting of their critiques changed, we noticed that the participation structures shifted from her position as a mentor to as a partner. We argue that this new classroom community differed from the community of school science in several ways: authority was shared, epistemic goals were valued, and authentic problems were investigated. These new instructional objectives are consistent with the standards movement in the United States and the teacher's own experiences and goals. Highlights: Student participation in argumentation increased dramatically over time. Teacher scaffolding faded in response to increased student participation. The teacher used directives based on personal and disciplinary authority. These features characterized a community of scientific epistemic practices.